2020
DOI: 10.3389/fmicb.2020.01340
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Vesicles of Helicobacter pylori 7.13 as Adjuvants Promote Protective Efficacy Against Helicobacter pylori Infection

Abstract: Helicobacter pylori(H. pylori), a gram-negative bacterium in the human stomach with global prevalence, is relevant to chronic gastrointestinal diseases. Due to its increasing drug resistance and the low protective efficacy of some anti-H. pylori vaccines, it is necessary to find a suitable adjuvant to improve antigen efficiency. In our previous study, we determined that outer membrane vesicles (OMVs), a multicomponent secretion generated by gram-negative bacteria, of H. pylori were safe and could induce long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…OMVs from H. pylori 7.13 strain were found to induce immune responses in mice without causing mucosal inflammation [ 52 ]. Using H. pylori 7.13 OMVs as adjuvants with a vaccine derived from outer membrane proteins or whole cell vaccine also significantly improved the protective effect in immunized mice [ 53 ]. Notably, LPS or other lipids in OMVs might not have the immunostimulatory role while H. pylori 7.13 OMVs were applied as adjuvants [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OMVs from H. pylori 7.13 strain were found to induce immune responses in mice without causing mucosal inflammation [ 52 ]. Using H. pylori 7.13 OMVs as adjuvants with a vaccine derived from outer membrane proteins or whole cell vaccine also significantly improved the protective effect in immunized mice [ 53 ]. Notably, LPS or other lipids in OMVs might not have the immunostimulatory role while H. pylori 7.13 OMVs were applied as adjuvants [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using H. pylori 7.13 OMVs as adjuvants with a vaccine derived from outer membrane proteins or whole cell vaccine also significantly improved the protective effect in immunized mice [ 53 ]. Notably, LPS or other lipids in OMVs might not have the immunostimulatory role while H. pylori 7.13 OMVs were applied as adjuvants [ 53 ]. Lipoprotein 20 (Lpp20) located on the surface of H. pylori OMVs was previously identified as a vaccine candidate which elicited a strong immune response in mice and the antibody against Lpp20 effectively lowered the colonization of H. pylori SS1 strain [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial components, such as cholera toxin and E. coli heat-labile enterotoxin, can also be used as adjuvants to boost the mucosal vaccination against H. pylori in mice [ 33 ], but enterotoxicity limits their clinical applications. Outer membrane vesicles of H. pylori were reported as non-toxic adjuvants to induce long-term protection with humoral and Th-1 immunity against H. pylori in mice [ 34 ]. Lipids are one component of the outer membrane vesicles of Gram-negative bacteria, and play roles in immune regulation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis demonstrated that vaccines with H. pylori -OMVs induced a Th2 and Th17 biased immunity, increasing cell mediated and humoral immunity, which reduces H. pylori colonization in a mouse model. Consequently, H. pylori -OMVs are effective adjuvants for these types of vaccines [ 180 ].…”
Section: Helicobacter Pylori -Outer Membrane Vesicles and Extracellular Vesicles From Helicobacter Pylori Infmentioning
confidence: 99%